Can the technique of knee wrap placement affect the maximal isometric force during back squat exercise? - Marchetti, P. H.; de Jesus Pereira Matos, V.; Soares, E. G.; da Silva, J. J.; Serpa, É. P.; Corrêa, D. A.; Martins, G.; de Barros Vilela Junior, G.; Gomes, W. A. (International Journal of Sports Science, 2015)
The aim of this study was to investigate the acute effects on maximal isometric force with two different techniques of knee wraps placement (spiral and X) during back squat exercise. Twenty-one physical active participants were evaluated during this study. The back squat exercise position was set up individually, guaranteeing their thigh parallel to the floor, the arms crossed on the chest, and the feet were kept always in the same position for all trials and conditions. All subjects performed three maximal isometric back squat contractions in 4 different conditions: without knee wrap (WKW), with spiral knee wrap technique (SKW), with X knee wrap technique (XKW) and tensor (T). The peak force was acquired at a 100Hz sampling frequency, during 3 seconds, 5 minutes of resting and all conditions were randomized. The Rating of Perceived Exertion (RPE) was evaluated after each trial and condition. The results shows significant differences for peak force between conditions SKW vs WKW (P=0.044, ES=0.55, delta%=10.8%), and XKW vs WKW (P=0.009, ES=0.62, delta%=13.6%). The use of different knee wrap techniques (spiral and X techniques) presented an effective carry-over effect, but without differences between techniques, and the RPE was similar in all conditions.